Os resultados da aplicação de estratégias de leitura para a formação do leitor competente - Vieira, Ana Paula de Oliveira Lopes (2020)
This study focuses on the development of Reading comprehension, based on practices carried out by Portuguese and Science teachers with exposition texts. Teachers from different subjects developed the activities and they used different strategies. This research supports the hypothesis that reading practices that involve the application of interdisciplinary strategies and procedures contribute to the learning process. The interpretative methodology was used, this means that quantitative data is in favor of qualitative reflections, under the socio-interactive perspective, based on the studies by Cardoso Silva (2006), Sayeg Siqueira (1997), Marcuschi (2008), Solé (1992) and Fazenda (2008). The reflections refer to textual organization, processes of comprehension, intertextual and interdisciplinary associations. The study presents a parallel between the development of linguistic studies and some reading approach models. Topics on comprehension processes, previous knowledge, textual structures, objectives and expectations of the reader, reading strategies, reflections on reading practices proposed in textbooks and interdisciplinary in Education are highlighted. It addresses teacher´s teaching strategies as a reader model so that the student develops and selects his own strategies until he becomes an autonomous reader. In addition, this investigation argues that being knowledgeable about textual structures and the confluence between skills from the Portuguese curriculum and skills from different subjects contribute to the development of reading comprehension